2019
DOI: 10.1111/jfpe.13035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various thermal processing methods on the shelf‐life and product quality of vacuum‐packaged braised beef

Abstract: The aim of this article was to compare the effects of three different heating methods; water bath (WB), radio frequency (RF), microwave (MW), and their combinations (WB–RF, WB–MW, RF–MW) on reducing bacterial load, extending shelf‐life, and preserving quality (color, texture, peroxide value, and smell) of vacuum packed braised beef. The thermally processed samples were stored at 37°C, and the total number of bacterial colonies, pH, color, texture, and smell profiles was measured and analyzed. WB–RF heating was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…Likewise, Wang et al. (2019) found that beef treated with microwaves received significantly lower liking scores along with increased perceptions of hardness than beef treated with other processing methods across a variety of sensory variables. Participants also reported that spiciness and heat were overpowering flavors in the herb meals, but not necessarily in an appealing way.…”
Section: Resultsmentioning
confidence: 97%
“…Likewise, Wang et al. (2019) found that beef treated with microwaves received significantly lower liking scores along with increased perceptions of hardness than beef treated with other processing methods across a variety of sensory variables. Participants also reported that spiciness and heat were overpowering flavors in the herb meals, but not necessarily in an appealing way.…”
Section: Resultsmentioning
confidence: 97%
“…For example, Wang et al. (2019) observed a significantly higher peroxide value in a water bath thermal sterilization group than that detected in the control group, which indicated that lipid oxidation in the vacuum‐packaged braised beef was accelerated via water bath thermal sterilization. In addition, Song et al.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been performed to analyze the effects of thermal processing on the flavor profile, shelf‐life, texture, and sensory characteristics of meat and meat products (Barbosa‐Cánovas et al., 2014; Wang et al., 2019). For example, Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…With Tan sheep ribs as raw materials, hand grab mutton (HGM) is a traditional boiled meat product with national characteristics in Northwest China. At present, most of the HGM products sold in the market use the “soft can” production technology to extend the shelf life, but the high-temperature and high-pressure sterilization has seriously damaged its flavor, which is not conducive to the development of Tan sheep meat processing industry ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%